Indian Economy and Small Business Administration: Umbrella Cover to SSI Sector - Tyagi, Ruchi; Sharma, Tanuj (Journal of Commerce and Trade, 2007)
The present work throws light, in general, on Small Scale Industry in India and role of Government to enhance the SSI sector, the present work will discuss the role of SSI along with general economy of the country. Further the paper present the factors contributing in marking global presence of Indian sports goods industry which falls under the purview of SSI .Indian sports Goods Industry is mainly concentrated in Jalandhar and Meerut. The Sports Goods Industry in India has made its global presence with its export. The present work outlines the factors, which have contributed to such a global presence.